Life Kinetic Training And Accuracy Of Overhead Lob Strokes Of Badminton Athletes - Alia Nur Pathonah; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (UNIVERSITAS NEGERI MAKASSAR, 2024)
Badminton players often give less attention to psychological training, resulting in various problems such as lack of concentration. To overcome this problem, life Kinetik training is proposed as a solution. This study aims to examine the difference in the effect of life Kinetik training on the accuracy of overhead lob shots of badminton athletes. The method used in this study is a quantitative experiment using a posttest-only control group design. Researchers provide treatment in the form of kinetic life training. The instrument used can smash accuracy. The research sample consisted of 10 athletes, 5 male and 5 female. Data analysis was carried out using the Independent Samples Test. The results showed that there was a significant effect of life Kinetik training on the accuracy of overhead lob shots for badminton athletes. Thus, it can be concluded that life Kinetik training is one method that can be used to improve technical skills in badminton, especially overhead lob shots